Best Practices in Relationship Education Focused on Intimate Relationships. Issue 3 (18th December 2019) - Stanley, Scott M.; Carlson, Ryan G.; Rhoades, Galena K.; Markman, Howard J.; Ritchie, Lane L.; Hawkins, Alan J.
Abstract : Relationship education is widely used to help people develop and sustain healthy romantic relationships. We first provide a review on the current state of evidence and key issues in the field, laying a foundation for suggesting specific best practices in relationship education. We focus on services provided to couples but also address the burgeoning field of relationship education with individuals. Although there are many gaps in the knowledge informing best practices—such as mechanisms of effect and dose—decades of research and experience provide a strong basis for specific recommendations. The hallmark of an evidence‐based, best‐practice approach lies in making thoughtful decisions based on current knowledge, the goals of the effort, the population served, and available resources.